Atorvastatin prevents amyloid-β peptide oligomer-induced synaptotoxicity and memory dysfunction in rats through a p38 MAPK-dependent pathway - Zhang Ling-ling; Sui Hai-juan; Liang Bing; Wang Han-ming; Qu Wen-hui; Yu Sheng-xue; Jin Ying (Acta Pharmacologica Sinica, 2016)
Ling-ling ZHANG, Hai-juan SUI, Bing LIANG, Han-ming WANG, Wen-hui QU, Sheng-xue YU, Ying JIN* Department of Pharmacology, Liaoning Medical University, Jinzhou 121001, China Aim: To investigate whether atorvastatin treatment could prevent Aβ1-42 oligomer (AβO)-induced synaptotoxicity and memory dysfunction in rats, and to elucidate the mechanisms involved in the neuroprotective actions of atorvastatin. Methods: SD rats were injected with AβOs (5 nmol, icv). The rats were administrated with atorvastatin (10 mg·kg-1·d-1, po) for 2 consecutive weeks (the first dose was given 5 d before AβOs injection). The memory impairments were evaluated with Morris water maze task. The expression of inflammatory cytokines in the hippocampus was determined using ELISA assays. The levels of PSD-95 and p38MAPK proteins in rat hippocampus were evaluated using Western blot analysis. For in vitro experiments, cultured rat hippocampal neurons were treated with AβOs (50 nmol/L) for 48 h. The expression of MAP-2 and synaptophysin in the neurons was detected with immunofluorescence. Results: The AβO-treated rats displayed severe memory impairments in Morris water maze tests, and markedly reduced levels of synaptic proteins synaptophysin and PSD-95, increased levels of inflammatory cytokines (IL-1β, IL-6 and TNF-α) and p38MAPK activation in the hippocampus. All these effects were prevented or substantially attenuated by atorvastatin administration. Pretreatment of cultured hippocampal neurons with atorvastatin (1 and 5 µmol/L) concentration-dependently attenuated the AβO-induced synaptotoxicity, including the loss of dendritic marker MAP-2, and synaptic proteins synaptophysin and PSD-95. Pretreatment of the cultured hippocampal neurons with the p38MAPK inhibitor SB203580 (5 µmol/L) blocked the AβO-induced loss of synaptophysin and PSD-95. Conclusion: Atorvastatin prevents AβO-induced synaptotoxicity and memory dysfunction through a p38MAPK-dependent pathway. Keywords: Alzheimer’s disease; atorvastatin; hippocampus; learning and memory; synapse; amyloid-β peptide; synaptophysin; PSD-95; cytokine; p38 MAPK This work was supported by grants from the Education Commission of Liaoning Province (LT2010064) and Liaoning Medical University (2012005). * To whom correspondence should be addressed. E-mail jyjinying1130@163.com Received 2013-10-14 Accepted 2013-12-27